The pact with hidden powers at the heart of modern experience - Fantini Da Silva, Lucas Silveira [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2020)
The metaphor of the sorcerer who are not able to control the occult powers called up by his own spell is brought by Marx to illustrate the relations of production in the Modern bourgeois society. This paper intends to associate the Marxist metaphor with the constitution of the Modern experience conveyed by Goethe's Faust in order to highlight the evil and demonic aspects inherit to the will of development encouraged by Capitalism in the Modern society. Such propositions have been based on the work of the following Marxist Critics: Marshall Berman, who deals with the idea of Modern development in Goethe's Tragedy, and Terry Eagleton, whose ideas on the concept of Tragedy approach the concept of Demonic.
Keywords: Demonic; Goethe; Marx; Modernity; Tragedy